2017
DOI: 10.4103/ijabmr.ijabmr_130_17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrated teaching sessions for comprehensive learning and rational pharmacotherapeutics for medical undergraduates

Abstract: Background:It is postulated that integrated teaching method may enhance retention of the knowledge and clinical applicability of the basic sciences as compared to the didactic method.Aim:The present study was undertaken to compare the integrated teaching method with the didactic method for the learning ability and clinical applicability of the basic sciences.Materials and Methods:The 2nd year MBBS students were divided into two groups randomly. The study was conducted into two stages. In the first stage, conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This might be useful to improve their prescription skills and to be a better-qualified health professional. 8 In this study around 55% students opined against the statement that the subjects of different phases are arranged sequentially in curriculum (Table 2). Same type of result was revealed by another study where about 90% teachers passed opinion for rearrangement of subjects of 2nd and 3rd phase.…”
Section: Discussionmentioning
confidence: 76%
“…This might be useful to improve their prescription skills and to be a better-qualified health professional. 8 In this study around 55% students opined against the statement that the subjects of different phases are arranged sequentially in curriculum (Table 2). Same type of result was revealed by another study where about 90% teachers passed opinion for rearrangement of subjects of 2nd and 3rd phase.…”
Section: Discussionmentioning
confidence: 76%
“…This percentage is higher than a similar study in Rajasthan, India. 17 However, other studies have reported more than 90% percent students agreeing to this statement. 18 , 19 Score for ‘promoting critical thinking’ was less than that of a similar study conducted in India.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, the means scores of the respondents' views regarding the future MBBBS course should adopt 'Integrated teaching' instead of traditional 'discipline based teaching' was 3.47 (Table1); which indicates that they were highly motivate for integrate teaching in future. Integrated teaching had potential to improve the knowledge, skills, and comprehensive learning, the students are benefitted if the planning and implication of integrated teaching are done properly, it may lead to better learning outcomes; this might be useful to improve their skills as better qualified health professional 8 . It was also mentioned that integrated curricula have been well-organized for effective clinical reasoning instead of the way basic sciences and clinical sciences traditionally taught as separate disciplines 9 .…”
Section: Discussionmentioning
confidence: 99%